A Discussion of Klass Landsman's Criticisms of the Fine-Tuning Argument. Issue 2 (2nd April 2020) - Chan, Kai-Yan; Chan, Man-Ho
ABSTRACT: Recently, Klass Landsman has published an article to argue that cosmic fine-tuning is neither a piece of good evidence for the design hypothesis nor a piece of good evidence for the multiverse hypothesis. In this article, we will focus on his criticisms of the fine-tuning design argument and provide a critical discussion on his arguments. We show that none of his criticisms are cogent.